ALGORITMA UNTUK MATCHING PADA SISTEM PENULISAN ULANG EKSPRESI - Slamet Santosa; Anton Setiawan Honggowibowo (Universitas Ahmad Dahlan, 2005)
Matching process in tree is finding subtree in a given tree which to be replaced to variables those occur in pattern tree. It is an important problem that occurs as a crucial operation in functional and equational programming such as Term Rewriting System. We present an algorithm for matching process on such term in tree based on pattern matching. We linearize both given tree and pattern tree into string representation by using Euler technique and and apply prefix-sum to computers the rank of all linearized edge. And then we do matcing on string sequential.